Ensaios sobre crescimento, restrição ao balanço de pagamentos e distribuição de renda em abordagem Stock-Flow Consistent (SFC) - Santos, Julio Fernando Costa (2017)
The present thesis consists of three papers that have different general objectives, but are linked by the Stock-Flow Consistent (SFC) approach. The first one, titled "An Alternate Algorithm for Mapping Stable Parameters in Stock-Flow Consistent (SFC) Models" solves a gap in the SFC models literature. A recurring criticism of such models is that the specific characteristics of a calibrated model cannot be generalized as general properties. In this way, the work innovates by creating new convergence criteria for steady state and through it to map parameters that lead to this condition. To show the convergence of results, we test the proposed algorithm and the usual method of stability analysis in equations to differences in the seminal model of the literature, Simplified Benchmark of Dos Santos and Zezza (2008). At the end, it is shown that the results are quite close. The second paper of the thesis worked the distributive conflict in SFC approach for a closed and financialized economy. In order to do so, we start with the Hein model (2012) and introduced some new features such as: interest rate endogenously determined by the inflation targeting regime, anti-cyclical mark-up for bank loans, business markup reacting to the profitability of financial decisions and the investment decision using the fixed capital yield differential and the capital-weighted average cost (WACC). It was concluded that the model had characteristics of the dominant wage-led regime, that is, even though there was possibility of finding profit-led regimes, the most common was the first. The third and final paper of this thesis tried to relax the hypothesis of exogeneity of the growth rate of the rest of the world existing in the growth models restricted by the balance of payments. To this end, two economies are constructed that transact among themselves, exchange financial flows and use a floating exchange rate regime. At the end of the paper, it can be concluded that the growth rate in line with Thirlwall's law is only observed in countries in which the size is small enough not to negatively influence the rate of growth of the partner product. That said, the work innovates by suggesting that the strategy of growing via export-led is a strategy valid for countries that are small when compared to the rest of the world and not effective for large countries.